2013
DOI: 10.4314/njp.v40i4.3
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life in school-aged children with and without asthma in Enugu, South East Nigeria

Abstract: Background: Identifying impaired quality of life is a recognized component of asthma management with no published data in Nigerian children with asthma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 18 publications
(24 reference statements)
1
7
0
Order By: Relevance
“…This was lower than Sweden [20] and Brazil. [21] This study found that the physical domain score was the most affected QOL domains which come in accordance with [4,22] [23] and Brazil. [21] This may be inferred to that physical function such as full participation in school sports activity, running and strenuous exercise is limited by asthma.…”
Section: Discussionsupporting
confidence: 78%
“…This was lower than Sweden [20] and Brazil. [21] This study found that the physical domain score was the most affected QOL domains which come in accordance with [4,22] [23] and Brazil. [21] This may be inferred to that physical function such as full participation in school sports activity, running and strenuous exercise is limited by asthma.…”
Section: Discussionsupporting
confidence: 78%
“…[47] Childhood bronchial asthma and quality of life Studies in Nigeria reported significant low quality of life (QoL) in children with asthma compared to children without asthma. [48][49][50] The QoL score was significantly affected by disease severity and level of symptoms control; the physical domain of QoL assessment was the most affected. [48][49][50] Also, female asthmatics were observed to be more affected than their male counterparts.…”
Section: Childhood Bronchial Asthma and School Absenteeismmentioning
confidence: 99%
“…[48][49][50] The QoL score was significantly affected by disease severity and level of symptoms control; the physical domain of QoL assessment was the most affected. [48][49][50] Also, female asthmatics were observed to be more affected than their male counterparts. [48][49][50] The caregivers of children with bronchial asthma were also reported to have low QoL which is related to the severity and control of their children/wards' disease.…”
Section: Childhood Bronchial Asthma and School Absenteeismmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite effective asthma medications available for symptom control, it has been reported globally that current treatments have not significantly reduced morbidity or mortality of the disease [ 10 ]. With this limitation therefore, there is an increasing need to use quality of life measures to evaluate the impact of asthma and its management on the daily lives and function of affected people and to identify the specific aspects of life with greater associated morbidity to enable effective management of the disease [ 11 - 13 ].…”
Section: Introductionmentioning
confidence: 99%